The Effects of E-leadership and TIC Competence on Motivation and Performance in Teachers: Case Study in Sukasari District, Sumedang Regency - Tri Hapsari, Kristanti; Sedarmayanti, Sedarmayanti; Saepudin, Didin (Annpublisher, 2023)
The world of education in the era of 4.0 is experiencing very rapid development wherethe role of education actors also continues to be updated. Rapid technological advances requireeducation actors to adjust. Advances in all-digital technology provide various conveniences incarrying out activities and can be carried out without being hindered by distance. Education actorsincluding principals and teachers who are the spearhead of education must make reforms in order toadapt to the era of globalization. Traditional leadership styles are felt to need to be updated withappropriate leadership styles, namely e-leadership that can improve teacher performance. However,the limited ability of the principal in mastering Technology, Information and Communication is anobstacle even though this is the basis for e-leadership. The government program was launched ondigitalization of education where the government will prepare schools and education actors toorganize digital-based learning to welcome the digital era. The problem lies in the competence ofhuman resources who are incompetent in facing the digitalization of education and also otherobstacles. The objective of this study should be to determine the extent to which e-leadershipinfluences teacher performance quality. This is quantitative descriptive study, and the instrument isin the form of a questionnaire. Techniques for data analysis include descriptive quantitative dataanalysis. The data's validity is determined by its dependability and validity. The findings revealedthat e-leadership had a beneficial impact on teacher performance. Path analysis reveals that thefactors of technology, information, and communication skill have a considerable impact on teacherperformance, with a positive connection direction.